Impact of AI Improving Sichuan Consumer Satisfaction in Online Experience Optimization and Service Efficiency - Jiahao Ye (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
This abstract explores the role of artificial intelligence (AI) in enhancing consumer satisfaction in Sichuan's online customer experience and service efficiency. With the rapid growth of e-commerce, understanding consumer preferences and behaviors has become crucial. AI technologies like chatbots, predictive analytics, and personalized recommendations are integrated into online platforms to streamline service delivery and improve user interactions. By leveraging data-driven insights, businesses can tailor their offerings to meet the specific needs of consumers, thereby increasing satisfaction levels. Furthermore, AI facilitates faster response times and more efficient problem resolution, leading to a seamless shopping experience. This study was conducted through an online questionnaire distributed to 380 Sichuan participants to measure their optimization and service efficiency satisfaction. The findings underscore that technical infrastructure, user acceptance and engagement, and service quality positively correlate with consumer satisfaction in AI experience improvement.